Au@Ag@Ag2S heterogeneous plasmonic nanorods for enhanced dye-sensitized solar cell performance. (June 2019) - Liu, Qisheng; Sun, Yiqiang; Yao, Mingming; Xu, Bo; Liu, Guangning; Hussain, Muhammad Bilal; Jiang, Kejian; Li, Cuncheng
Graphical abstract: Highlights: Novel Au@Ag@Ag2 S heterogeneous nanorods were synthesized for fabrication the DSSCs. The optimized blended amounts of Au@Ag@Ag2 S for the highest enhancement of the DSSCs were obtained. Strong SPR effects increase the light-harvest abilities of Au@Ag@Ag2 S-based DSSCs. The Au@Ag@Ag2 S with different aspect ratios can facilitate adjusting SPR effects for boosting the DSSC performance. Abstract: Au@Ag@Ag2 S heterogeneous nanorods (NRs) with two strong plasmonic absorptive bands were developed for boosting the performance of dye-sensitized solar cells, and the remarkably enhanced plasmonic devices were achieved. By doping different concentrations of the Au@Ag@Ag2 S NRs within the TiO2 photoanode layers, various enhanced effects of the plasmonic devices were obtained. With the incorporation of the typical Au@Ag@Ag2 S NRs (their aspect ratios: 2.7) into the TiO2 photoanodes, the top efficiency of 6.51% of the fabricated plasmonic photovoltaic devices at their doped concentrations of the 2.31% was observed, exhibiting dramatic 40% enhancement than that of the conventional dye-sensitized solar cells (bare device: 4.65%). Benefiting from effective surface plasmon effects of the Au@Ag@Ag2 S NRs, the light-harvesting abilities of photoanodes and dyes in devices are dramatically enhanced, which in return boost the whole performance of photovoltaic devices significantly.